Pengaruh Pertumbuhan Ekonomi Terhadap Pendapatan Asli Daerah Kabupaten/Kota di Provinsi Jambi - Ayu Desmawati; Zamzami Zamzami; Zulgani Zulgani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
This study aimed to analyze the effect of economic growth on revenue districts / cities in Jambi Province. The data used is data panel districts / cities in Jambi province during the Year 2007-2013. Data were analyzed using panel data regression. The study found that a significant effect of economic growth to local revenue. This means that the economic growth of the district/city has been effective in increasing revenue growth. In other words, economic growth has spread in the economic sector is a source of local revenue.